Special Interest Tourism Research Trends in Indonesian Journals: A Review from Design to Analysis - Muharis, Muharis; Muhammad Taufik; Bagas Anggara; Abdul Muhid (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
This study aims to map the trends and characteristics of special interest tourism research in Indonesia in the period 2020–2024. The method used is content analysis with a focus on six main aspects: number of publications per year, type of research, research subjects, tourism topics studied, data collection instruments, and data analysis methods. Data were obtained through a systematic search on Google Scholar on April 26, 2025 using the keyword "special interest tourism." From approximately 104,000 initial results, after filtering based on year of publication and title relevance, 74 data were obtained, of which only 42 articles were fully accessible and 34 of them were used as research samples. The results show fluctuations in publication trends, with significant spikes in 2023 and 2024. Qualitative research dominates, while quantitative and mixed methods are still minimal. The most frequently used instruments are observation sheets and triangulation, while common data analysis techniques include SWOT and qualitative descriptive. Government and tourists emerged as the most research subjects, reflecting a focus on tourist policies and experiences. The topics studied are very diverse, ranging from tourist behavior, environmental conservation, tourist villages, to tourism product innovation. This study concludes that special interest tourism is increasingly in demand as a field of study, but the methodological approach still tends to be exploratory and descriptive. It is recommended to strengthen quantitative and mixed-method methods and expand the focus of research on policy, creative economy, and sustainability. These results are expected to be an initial reference for researchers and stakeholders in developing more comprehensive special interest tourism research in the future.